PEMERINTAHAN ILAHI ATAS KERAJAAN MANUSIA: Psikologi Ibn â€˜Arabi tentang Roh - Noer, Kautsar Azhari (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2011)
This article is an attempt to explore especially the position and function of spirit (al-rÅ«h) in human being. Ibn â€˜Arabi describes analogically human being as a â€œhuman kingdomâ€ (al-mamlakah al-insaniyyah). Spirit is the king of the kingdom, the highest leader which is called the â€œvicegerent of Godâ€ (khalÄ«fatuâ€˜Llah) or shortly the â€œvicegerentâ€ (khalÄ«fah). This writing presents Ibn â€˜Arabiâ€™s view on the divine design and management of the world, and the central role the human model plays in the creative and governing process. The only way to reach the human perfection is divine governance (al-tadbÄ«rat al-ilahiyyah) of the human kingdom in which the spirit governs and controls the soul and body. This Sufi uses metaphors from worldly politics to illuminate details of the spiritual search.